Samvedna – Protecting the Child from Abuse - Govinda, Amita (THE PRIMARY TEACHER, 2006)
Eight year old Manju began her school life as a bubbly, outgoing child, who made friends easily with teachers and other children. Suddenly she began to spend her time sitting alone. Even during recess she sat alone. Her smile disappeared. The drastic change in her behaviour was noticed by her teacher. So, the teacher called Manju and spent sometime talking to her. During this interaction it was revealed how Manju had been abused by her own uncle. The teacher helped Manju to regain her confidence and Manju once again became her former self. Lakshmi initially did not bother too much when her five year old sonc omplained of pain. When the pain persisted she took him to the doctor. To her horror she came to know that her had son been abused by the boy who was looking after him.